Mammalian Chemical Genomics towards Identifying Targets and Elucidating Modes‐of‐Action of Bioactive Compounds. (7th December 2021) - Matsumoto, Ken; Yoshida, Minoru
Abstract: The step of identifying target molecules and elucidating the mode of action of bioactive compounds is a major bottleneck for drug discovery from phenotypic screening. Genetic screening for genes that affect drug sensitivity or phenotypes of mammalian cultured cells is a powerful tool to obtain clues to their modes of action. Chemical genomic screening systems for comprehensively identifying such genes or genetic pathways have been established using shRNA libraries for RNA interference‐mediated mRNA knockdown or sgRNA libraries for CRISPR/Cas9‐mediated gene knockout. The combination of chemical genomic screening in mammalian cells with other approaches such as biochemical searches for target molecules, phenotypic profiling, and yeast genetics provides a systematic way to elucidate the mode of action by converging various pieces of information regarding target molecules, target pathways, and synthetic lethal pathways. Abstract : Chemical genomic screens using shRNA or CRISPR/Cas9 sgRNA libraries in mammalian cultured cells play central roles in identifying modes of action of bioactive compounds. In this review, recent advances of chemical genomic approaches in mammalian cultured cells to identify the molecular target, modes of action, and synthetic lethal pathways of compounds of interest, with a focus on recent examples including our results are discussed.